Study on micro-structure and dynamic mechanical properties of machined surface layer by aluminum alloy 7050-T7451. (7th September 2018) - Xu, Nianwei; Pan, Yanan; Wang, Xiangyu; Fu, Xiuli
Abstract: Surface micro-structure of a machined workpiece has an important effect on functional performance. During machining, the change of grain size is closely related to dynamic mechanical properties. Turning experiment was conducted via changing turning speed and rake angle with aluminum alloy 7050-T745, and then ultra-depth microscope and transmission electron microscope (TEM) were used to observe and analyze the micro-structure and grain refinement of turning machined surface layer. Afterwards, under the same cutting condition, the DEFORM finite element simulation software was used to simulate the strain, strain rate, temperature and other dynamic mechanical properties in the plastic deformation zone. The results show that the dislocation multiplication is the main cause of grain refinement, and the change of dislocation density is directly related to the dynamic mechanical properties parameters. The turning speed is in negative linear correlation with strain, strain rate and the temperature, while the grain size on cutting surface layer is reduced along with the increase of turning speed.